Impact of urbanization on the ecological state of soils in the city of Uralsk - Gumarova, Zh. M.; Gubasheva, B. E.; Sungatkyzy, S.; Akkereyeva, E. K.; Sarsenbayev, A.U. (My University, 2021)
The soils of the city of Uralsk are currently experiencing a strong urban impact due to anthropogenic inputs of materials and atmospheric fallout. In this work, urban soils were studied selected in the zone of influence of gas stations, highways, as well as in public gardens and park named after Kirov. The soils of the urban environment are characterized by a special urban-anthropogenic layer, the presence of building and household inclusions and close proximity to communications, therefore, sampling was carried out in a layer of 0-20 cm. The determination of pollutants, heavy metals and oil products was carried out along with the study of biological activity and pH. The biological parameters of urban soils were determined by the rate of decomposition of linen tissue - cellulolytic activity. Measurements for heavy metals, pH and petroleum products were carried out by atomic absorption, fluorimetric and potentiometric methods. The analysis of the territories most susceptible to anthropogenic influences showed the least results in terms of changes in the weight of cellulosic materials, as well as the greatest excess of the maximum permissible concentrations for lead, zinc and cobalt and oil products. The clearly expressed excess testifies to a strong anthropogenic impact and deterioration of the soil condition, despite the occupation of green spaces in the squares named after Zh. Moldagulov, Isatay and Makhambet. At the same time, the soils of the Kirov Park, which are located far from potential sources of pollution and the absence of pollutants, have shown their recreational value in terms of improving the environment. Biological diagnostics of soils based on cellulolytic activity is a quite suitable and reliable indicator in the study of urban soils in the city of Uralsk.Почвы города Уральска в настоящее время испытывают сильное влияние города из-за антропогенного поступления материалов и атмосферных выпадений. В данной работе изучались городские почвы, отобранные в зоне влияния АЗС, автомагистралей, а также в скверах и парке им. Кирова. Почвы городской среды характеризуются особым городско-антропогенным слоем, наличием строительных и бытовых включений и близостью к коммуникациям, поэтому отбор проб проводился в слое 0-20 см. Определение загрязняющих веществ, тяжелых металлов и нефтепродуктов проводилось одновременно с изучением биологической активности и pH. Биологические параметры городских почв определялись скоростью разложения льняной ткани - целлюлозолитической активностью. Измерения тяжелых металлов, pH и нефтепродуктов проводились атомно-абсорбционным, флуориметрическим и потенциометрическим методами. Анализ территорий, наиболее подверженных антропогенным воздействиям, показал наименьшие результаты по изменению веса целлюлозных материалов, а также наибольшее превышение ПДК по свинцу, цинку, кобальту и нефтепродуктам. Ярко выраженное превышение свидетельствует о сильном антропогенном воздействии и ухудшении состояния почвы, несмотря на заселенность зеленых насаждений в скверах им. Ж. Молдагулов, Исатай и Махамбет. В то же время почвы Кировского парка, расположенные вдали от потенциальных источников загрязнения и отсутствия загрязняющих веществ, показали свою рекреационную ценность с точки зрения улучшения состояния окружающей среды. Биологическая диагностика почв по целлюлозолитической активности - вполне подходящий и надежный индикатор при изучении городских почв г. Уральска.
International Scientific and Practical Conference on Ensuring Sustainable Development in the Context of Agriculture, Green Energy, Ecology and Earth Science, ESDCA 2021
Keywords: импакт-фактор 2021 - --; зарубежное издание; конференции; скопус; загрязнение почвы; охрана окружающей среды; зко; почвоведение; scopus